The Responsibilities of the Directors of the Limited Liability Company to the credit of PT. Putera Daya Perkasa based on Act No. 40 of 2007 concerning Limited Liability Companies - Khairiyyah Annisa Someren Brand; Budi Santoso (Universitas Islam Sultan Agung, 2023)
The purpose of this study is to determine the position, role and responsibilities of the directors of a limited liability company in relation to credit in Indonesia, and to find out if there is an abuse of the authority of a limited liability company by directors who take refuge and like to take advantage of the weaknesses of the applicable laws and regulations. The limited liability company has obtained the status of a legal entity, meaning that liability is limited to the company's assets, but to avoid having company management in running the company deviate from the rule of law, the result is formulated that Act No. 40 of 2007 concerning Limited Liability Companies, in principle adheres to limited liability principle. Provisions in Article 3 paragraph (1). Limited responsibility for each board of directors.